The Impact of Migration on the Economic Conditions of Former Migrant Workers in Lakmaras Village, Lamaknen Selatan District, Belu Regency - Veronika Adriani Loe; Mikael Samin; Agustinus Hale Manek (Tinta Emas Institute, 2026)
This study aims to determine the impact of migration on the economic conditions of former migrant workers in Lakmaras Village, Lamaknen Selatan District, Belu Regency. The study was conducted from February to August 2025 using a quantitative approach. Primary data were obtained through questionnaires, interviews, and observations, while secondary data were collected from supporting documents and literature. The study sample consisted of 71 respondents, determined using the Yamane formula with a 10% margin of error. Data analysis was conducted using descriptive quantitative methods to describe the economic conditions of former migrant workers based on income, employment, education level, and asset ownership. The results indicate that migration has a significant and positive economic impact on former migrant workers. Migration enables them to accumulate assets such as land, houses, and vehicles, which serve as productive capital and improve family welfare. Furthermore, migration opens up opportunities for job diversification and increases household economic capacity. Overall, migration plays a strategic role in wealth formation, improving economic status, and contributing to local economic development. Future research is recommended to use a qualitative approach to deepen understanding of income management strategies and the challenges faced by former migrant workers.